Desmoglein compensation hypothesis fidelity assessment in Pemphigus - Sielski, Lauren; Baker, John; DePasquale, Michael C.; Attwood, Kristopher; Seiffert-Sinha, Kristina; Sinha, Animesh A. (Frontiers in Immunology, 2022)
The pemphigus group of autoimmune blistering diseases encompasses pemphigus vulgaris (PV) and pemphigus foliaceus (PF). Lesion location in pemphigus has been elegantly postulated by the Desmoglein Compensation Hypothesis (DCH), which references the distribution of desmoglein (Dsg) proteins in the epidermis along with a patient’s autoantibody profile to describe three different lesion phenotypes: PF is characterized by subcorneal lesions in the presence of anti-Dsg1 antibodies only, while lesions in PV are suprabasilar and accompanied by anti-Dsg3 antibodies only in mucosal PV, or both anti-Dsg3 and anti-Dsg1 in the case of mucocutaneous PV. While the validity of this hypothesis has been supported by several studies and is prominently featured in textbooks of dermatology, a number of logical inconsistencies have been noted and exceptions have been published in several small-scale studies. We sought to comprehensively assess the extent to which patient clinical and autoantibody profiles contradict the DCH, and characterize these contradictions in a large sample size of 266 pemphigus patients. Remarkably, we find that roughly half of active PV and PF patients surveyed present with a combination of lesion morphology and anti-Dsg3/1 levels that contradict the DCH, including: patients with a cutaneous only PV presentation, mucocutaneous disease in the absence of either Dsg3, Dsg1, or both, and mucosal disease in the absence of Dsg3 or presence of Dsg1. We also find stark differences in fidelity to the DCH based on ethnicity and HLA-association, with the lowest proportion of adherence in previously understudied populations. These findings underscore the need to expand our understanding of pemphigus morphology beyond the DCH, in particular for populations that have not been a focus in previous investigation.